P‐57: OLED Lighting Devices Fabricated by Flexography Printing of Silver Nanowire and Conducting Polymer. Issue 1 (June 2015) - Furukawa, Tadahiro; Kawamura, Norifumi; Inoue, Junichi; Nakada, Hitoshi; Koden, Mitsuhiro
Abstract : Non‐ITO transparent electrode technology is one of the emerging key technologies for next generation flexible organic electronics devices. As a novel non‐ITO transparent electrode, we developed a transparent electrode with a stacking structure composed of silver nanowire and transparent conducting polymer by using flexography printing. In addition, OLED devices were successfully fabricated on the developed transparent electrodes.